Adverse childhood experiences and common mental disorders among young people in Ethiopia: a cross-sectional study using WHO ACE-IQ - Clare Pain; Awoke Mihretu; Yishak Gezahegn; Benyam Worku (BMJ Open)
Objective This study aimed to explore adverse childhood experiences (ACEs) and their association with common mental disorders (CMD) among college students in Ethiopia.Design Cross-sectional study.Setting Addis Ababa University, College of Health Sciences.Participants A total of 345 participants completed the whole questionnaire.Methods and materials The study used a stratified random sampling technique. Data were gathered through self-administered questionnaires. The instruments used included adapted sociodemographic questions, the ACEs International Questionnaire, the Patient Health Questionnaire, the Generalized Anxiety Disorder Scale and a brief tool for assessing substance use. To examine the relationship between ACEs and various independent variables, both binary and multivariate logistic regression analyses were employed.Result In the total sample (n=345), the participant’s mean age was 22.2 (± 2.03), with the majority being females (58%). About 16% of the participants reported depression symptoms and 14.2% had anxiety. The majority of the participants (80%) had at least one ACE and one quarter (25.2%) of the participants had experienced four or more ACEs. The most prevalent type of ACE was community violence (35.4%). One fifth (20%) of the participants had reported having experienced childhood sexual abuse. After controlling for confounding variables, those with four or more ACEs were 6.17 times (adjusted OR (aOR) 6.17; 2.51, 15.18) and 6.0 times (aOR 6.0; 2.25, 16.02) more likely to have depression and anxiety, respectively.Conclusion There was a dose-response relationship between ACEs and both anxiety and depression. Identifying and preventing ACEs at an early stage could contribute to reduce depression and anxiety among young people. Efforts to prevent ACEs should target not only individuals but also extend to households and communities.